Thermodynamics of photoelectric devices - Samuel L. Jacob; Artur M. Lacerda; Yonatan Dubi; John Goold (Physical Review Research)
We study the nonequilibrium steady state thermodynamics of a photodevice which can operate as a solar cell or a photoconductor, depending on the degree of asymmetry of the junction. The thermodynamic efficiency is captured by a single coefficient of performance. Using a minimal model based on a two-level system, we show that when the Coulomb interaction energy matches the transport gap of the junction, the photoconductor displays maximal response, performance, and signal-to-noise ratio, while the same regime is always detrimental for the solar cell. Nevertheless, we find that the Coulomb interaction is beneficial for the solar cell performance if it lies below the transport gap. Our work sheds important light on design principles for thermodynamically efficient photodevices in the presence of Coulomb interactions.